Birds in winter : surviving the most challenging season - Pasquier, Roger F. (Princeton University Press, 2019)
How birds have evolved and adapted to survive winterBirds in Winter is the first book devoted to the ecology and behavior of birds during this most challenging season. Birds remaining in regions with cold weather must cope with much shorter days to find food and shelter even as they need to avoid predators and stay warm through the long nights, while migrants to the tropics must fit into very different ecosystems and communities of resident birds. Roger Pasquier explores how winter affects birds' lives all through the year, starting in late summer, when some begin caching food to retrieve months later and others form social groups lasting into the next spring. During winter some birds are already pairing up for the following breeding season, when health through the winter contributes to nesting success. Today, rapidly advancing technologies are enabling scientists to track individual birds through their daily and annual movements at home and across oceans and hemispheres, revealing new and unexpected information about their lives and interactions. But, as Birds in Winter shows, much is visible to any interested observer. Pasquier describes the season's distinct conservation challenges for birds that winter where they have bred and for migrants to distant regions. Finally, global warming is altering the nature of winter itself. Whether birds that over millennia have evolved to survive this season can now adjust to a rapidly changing climate is a problem all people who enjoy watching them must consider. Filled with elegant line drawings by artist and illustrator Margaret La Farge, Birds in Winter describes how winter influences the lives of birds from the poles to the equator.